Notes on Anti-Semitism in Modern Greece - Kitroeff, Alexander (Études helléniques / Hellenic Studies, 1997)
This short article offers a preliminary interpretation of the nature of Christian-Jewish relations and of the causes of anti-Semitism in modern Greece. Focusing primarily in the period beginning in the 1920s and ending in the 1940s, it argues that both the positive and the negative sides to this relationship have been politically determined and that anti-Semitism in Greece has relied relatively little on religious or philosophical/racial theories. The article is closely based on a presentation the author made to a conference held by the Hellenic Literature Society in New York City in the Fall of 1996. Since this is a synthesis of the author’s own research and of the work of authors mentioned in the article, there are no footnote.